Total Quality Management in the Utilization of Educational Reports at SMAS Santo Yosef and SMAN 4 Mandau, Bengkalis Regency - Christine, Jene; Raharja, Setya (FKIP - Universitas Riau, 2025)
This study analyzes: (1) the implementation of Total Quality Management (TQM) principles in the utilization of Education Reports, (2) school strategies for integrating Education Report results into planning and TQM-based quality improvement, and (3) supporting and inhibiting factors in the application of TQM related to the use of Education Reports as tools for sustainable and systematic quality enhancement at SMAS Santo Yosef and SMAN 4 Mandau, Bengkalis Regency. This research employs a descriptive qualitative approach with principals, teachers, education staff, school committee members, and students as subjects. Data were collected through interviews, observations, and document analysis, with source and technique triangulation used to ensure credibility. Data were analyzed through data condensation, data display, and conclusion drawing/verification. The findings show that both schools use Education Report data as a basis for planning and designing quality improvement programs, supported by strong collaboration among school stakeholders. Annual evaluations and follow-ups based on Education Reports help maintain consistency in quality improvement and strengthen a culture of continuous quality. However, limited time, resources, and uneven understanding of quality management roles hinder optimal TQM implementation, indicating the need for more systematic integration of TQM and more intensive evaluation cycles.